2010
DOI: 10.1242/jcs.065698
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping and distinct functions for cofilin, coronin and Aip1 in actin dynamics in vivo

Abstract: SummaryActin-filament disassembly is crucial for actin-based motility, to control filament network architecture and to regenerate subunits for assembly. Here, we examined the roles of three actin cytoskeletal proteins, coronin, cofilin and Aip1, which have been suggested to combine in various ways to control actin dynamics by promoting or regulating disassembly. We studied their functions during the endocytosis process in budding yeast, where actin-filament dynamics at the cortical actin 'patch' contribute to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
91
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(101 citation statements)
references
References 61 publications
9
91
1
Order By: Relevance
“…Here, we showed that the onset of actin polymerization did indeed precede the final burst of dynamin recruitment by ,20 s, consistent with a role for actin polymerization early in the invagination stage of CME and the later recruitment of dynamin to the deeply invaginated CCP, where it executed scission [9] (Figure 8). We also discovered that coronin1B and cofilin, proteins involved in the down-regulation of actin polymerization and F-actin severing, respectively, were recruited at later time points, again similar to yeast endocytosis [24,72,73]. Third, it was proposed that scission of endocytic invaginations in yeast is triggered by a PI-phosphatase that dephosphorylates PiP2 and thus induces a line tension in the membrane neck [74].…”
Section: Similar To Yeast Mammalian Cme Has a Modular Designmentioning
confidence: 64%
“…Here, we showed that the onset of actin polymerization did indeed precede the final burst of dynamin recruitment by ,20 s, consistent with a role for actin polymerization early in the invagination stage of CME and the later recruitment of dynamin to the deeply invaginated CCP, where it executed scission [9] (Figure 8). We also discovered that coronin1B and cofilin, proteins involved in the down-regulation of actin polymerization and F-actin severing, respectively, were recruited at later time points, again similar to yeast endocytosis [24,72,73]. Third, it was proposed that scission of endocytic invaginations in yeast is triggered by a PI-phosphatase that dephosphorylates PiP2 and thus induces a line tension in the membrane neck [74].…”
Section: Similar To Yeast Mammalian Cme Has a Modular Designmentioning
confidence: 64%
“…Activation of Arp2/3 Is Required for Normal Actin Patch Dynamics in Budding Yeast-In wild-type S. cerevisiae, actin and actin-binding proteins assemble to their peak concentrations in the patches in about 8 s, after which the patches separate from the cortex and move into the cytoplasm (15,19,21). In the crn1⌬ strain, the duration of the assembly phase of an average actin patch is increased by 2 s (13,19).…”
Section: Resultsmentioning
confidence: 99%
“…In the crn1⌬ strain, the duration of the assembly phase of an average actin patch is increased by 2 s (13,19). To determine whether activation of Arp2/3 complex by Crn1 influences the dynamics of patch assembly, we deleted CRN1 from a haploid strain and reintegrated mutant or wild-type CRN1 genes under control of their native promoters into the leu2-3,112 locus (see supplemental Table S1 for all strains used in this study).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations